Improving a Coffee Cooperative Operations Using Online Traceability Systems - Dana Karningsih Putu; Santhi Dewi Dyah; Kusumawardani Rindi; Salsabila Akhmad Rana (BIO Web of Conferences)
Coffee plays a significant role for many smallholder farmers as their source of income. Global practices in the coffee business need quality assurance, and safety across its supply chain, which could be facilitated through traceability systems. Tracking coffee from the producer to the consumer could encourage eco-friendly farming practices and empower consumers with insights to make ethical purchasing choices. Therefore, traceability systems support coffee business requirements and environmental sustainability across its value chain. Wonosalam coffee cooperative, a group of coffee farmers and producers in Indonesia, has started providing simple traceability reports to comply with customer requirements. The report is manually hand-written on the coffee package directly. To better manage the growing coffee business complexity and provide a proper report to customers, this study proposes to develop a mobile phone-based traceability with a QR code system. This application is developed using a User-Centered-Design approach to ensure its suitability to coffee cooperative member requirements. The application has passed the user test with a high user satisfaction level, based on the System Usability Scale. This traceability system application is then extended with quality control and assurance features that enable coffee cooperative members to monitor and improve their business seamlessly.